The Readiness of Psychiatrists to Implement Psychedelic-Assisted Psychotherapy - Page, Lisa A.; Rehman, Ahmad; Syed, Habib; Forcer, Kathryn; Campbell, Graham (Frontiers in Psychiatry, 2021)
Introduction: Psychedelic-assisted psychotherapy is a promising approach in psychiatry; evidence is growing and it may not be long before mainstream services are expected to offer it to selected patients. This pilot study examined the attitudes and knowledge of NHS psychiatrists of all levels towards psychedelic-assisted psychotherapy and explored potential barriers and facilitators to its implementation. Methods: A mixed-methods approach was adopted, using a cross-sectional survey and focus groups. All psychiatrists in one NHS mental health trust were approached by email to participate. The survey was analysed using a simple descriptive approach and thematic analysis was used for the focus groups. Results: 83 (25.7%) psychiatrists participated in the survey. All psychiatrists were familiar with one or more psychedelic substances. Although 77.2% felt that there should be a role for controlled or therapeutic use of psychedelics, trainees appeared better informed than non-training grade psychiatrists. Psychiatrists of all grades did not feel prepared to participate in the delivery of psychedelic-assisted psychotherapy. Thematic analysis of the focus groups identified three main themes in relation to psychedelic-assisted psychotherapy: ‘need for knowledge’, ‘openness to change’ and ‘uncertainty’. Discussion: NHS psychiatrists are positive about the potential for psychedelic-assisted therapy to advance psychiatric practice. However, psychiatrists are lacking in confidence or preparedness to implement this treatment should it become a mainstream option and significant training needs were identified. Thematic analysis highlighted the need for societal shifts as well as professional ones.